THE EFFECT OF INDEPENDENT LEARNING ON ARABIC LEARNING ACHIEVEMENT AT INTEGRATED ISLAMIC ELEMENTARY SCHOOL - Almaulidia, Sarah; Nur Rois, Ikhwan (JMIE (Journal of Madrasah Ibtidaiyah Education), 2023)
This study aims to determine the level of influence of learning independent on Arabic learning achievement in sixth grade students at SDIT Al-Khairaat Yogyakarta in the 2021-2022 academic year. This type of research is quantitative research with a regression approach using a sample of 59 respondents taken by random sampling technique. Data collection techniques used were questionnaires, observation, interviews, and documentation. The data analysis technique uses two tests, namely: assumption test and hypothesis test with a simple linear regression approach, regression coefficient significance test and determination test. The results of this study indicate that there is a significant influence between learning independence on Arabic learning achievement with the results of the regression equation; Y = 49.566 + 0.272X, and the coefficient value is 0,344 > 0,05 with an influence percentage of 16%.